Role of hydrops MRI in differentiating between Menière’s disease and vestibular migraine: a prospective study - Anja Bernaerts; Morgana Sluydts; Vincent Liégeois; Catherine Blaivie; Floris L. Wuyts; Floris L. Wuyts; Joost van Dinther; Andrzej Zarowski; Filip Deckers; Bert De Foer (Frontiers in Neurology)
ObjectiveWe investigated the effectiveness of delayed post-gadolinium (Gd) three-dimensional (3D) sampling perfection with application-optimized contrasts using different flip angle evolution (SPACE) fluid-attenuated inversion recovery (FLAIR) sequence to differentiate between Menière’s disease (MD) and vestibular migraine (VM) in a prospective study.MethodsA total of 31 patients—15 with MD (10 with definite MD and 5 with probable MD) and 16 with VM (9 with definite VM, 7 with probable VM)—were prospectively enrolled between January 2019 and December 2022. The female-to-male ratio in the MD group was 7:8, while in the VM group, it was 14:2. All patients underwent a 3D SPACE FLAIR sequence and a 3D SPACE T2 sequence 4 h after intravenous (IV) injection of a single dose of gadobutrol (1.0 mmoL/mL). Cochlear endolymphatic hydrops (CEH), vestibular endolymphatic hydrops (VEH), and asymmetrical perilymphatic enhancement (PLE) were assessed.ResultsNone of the VM patients showed signs of CEH, VEH, or increased PLE. However, in the MD group, only two patients had normal CEH, one patient had normal VEH, and six patients demonstrated equal PLE in both ears. The logistic regression analysis using both VEH and CEH correctly predicted all cases of MD and VM, achieving 100% diagnostic accuracy for both conditions. However, using only CEH, VEH, or PLE as diagnostic criteria resulted in misclassifications: two patients were incorrectly classified as having VM based on CEH, one based on VEH, and six based on PLE. These results highlight the superior diagnostic power of the combination of CEH and VEH in logistic regression analysis.ConclusionThe combination of CEH and VEH allows for 100% accurate identification of VM and MD. This approach facilitates a reliable differential diagnosis of MD and VM when used in the appropriate clinical setting.Clinical relevance statementThis study demonstrates that hydrops magnetic resonance imaging (MRI) can accurately differentiate MD from VM. Therefore, hydrops MRI can obviate the need for trial medication in cases with clinically ambiguous findings.